PREVALENCE OF GASTROINTESTINAL NEMATODE INFECTION IN BALI CATTLE IN JAYA MAKMUR VILLAGE LABANGKA SUB-DISTRICT SUMBAWA BESAR REGENCY - Baiq Yustika Ratu; Ida Ayu Pasti Apsari; I Made Dwinata (Fakultas Kedokteran Hewan Universitas Udayana, 2024)
Infection by nematode worms in Bali cattle can lead to various health issues, such as weight loss, diarrhea, reduced production, and even death in severe cases. The aim of this study is to determine the prevalence of infection and identify the types of nematode worms in the digestive tract of Bali cattle in Jaya Makmur Village, Labangka District, Sumbawa Besar Regency. A total of 100 fecal samples were used, selected using a purposive sampling method. Fecal examination was conducted using the flotation method. The results of the study showed that the prevalence of nematode worm infection in Bali cattle was 62%. The types of nematode worms infecting were Strongyle type (58%), Toxocara vitulorum (8%), and Trichuris sp. (5%). The chi-square test showed no significant relationship (P>0.05) between age and gender with the prevalence of nematode. The prevalence of nematode infections in Bali cattle in Desa Jaya Makmur is quite high. Further research on the impact of the infection needs to be conducted, and farmers need to improve the maintenance system by cleaning the barns, providing quality feed, and administering regular treatments to reduce nematode infections.